STATUS STOK BELANGKAS PADI (CARCINOSCORPIUS ROTUNDICAUDA) DI PERAIRAN KOTABARU, KALIMANTAN SELATAN, INDONESIA - Yogho Faiz Riadha; Ledhyane Ika Harlyan; Muhammad Arif Rahman; Feni Iranawati; Alvina Maharani; Dewa Gede Raka Wiadnya (Politeknik Kelautan dan Perikanan Sorong, 2026)
Small-scale shrimp fisheries in Kotabaru Regency, South Kalimantan, not only serve as a vital source of local economic support but also pose potential threats to the sustainability of non-target species caught as bycatch, including the mangrove horseshoe crab (Carcinoscorpius rotundicauda), which is protected in Indonesia. This study aimed to assess the stock status of Carcinoscorpius rotundicauda captured as bycatch in local shrimp fisheries. Data was collected from January to March 2025, with a total of 125 individuals. Results indicated that Carcinoscorpius rotundicauda exhibited a negative allometric growth pattern. The length at first capture ( ) was found to be lower than the length at first maturity ( ). Specifically, was 11.85 cm for trammel nets and 13.52 cm for crab gillnets, while was 17.59 cm, suggesting that most individuals caught as bycatch had not yet reached gonadal maturity. This condition reflects fishing pressure on the population. Using the Length-Based Spawning Potential Ratio (LB-SPR) method to assess stock status of mangrove horseshoe crab that indicating overexploited (SPR<20). These findings highlight the urgent need for sustainable fisheries management, including regulations on fishing gear and protection measures for bycatch species such as Carcinoscorpius rotundicauda in Kotabaru waters.